Adsorptive Distillation of Bioethanol from Cherry Fruit and Pineapple Peel Using Mg/Al-Hydrotalcite for Ethanol Enrichment (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Bioethanol production from fruit biomass waste is a promising and sustainable approach to addressing both energy crises and environmental concerns. This study aims to evaluate the characterization of Mg/Al-hydrotalcite as an adsorbent, determine the optimum adsorption time and adsorbent mass for enhancing bioethanol concentration, and assess the physical properties of the resulting bioethanol. Mg/Al-hydrotalcite was synthesized using the coprecipitation method and characterized. The XRD analysis showed three major diffraction peaks at 2θ = 11.55°, 23.36°, and 34.89°, which are consistent with the standard diffractogram pattern of Mg/Al-hydrotalcite (JCPDS No. 89-0460). FTIR spectra confirmed the presence of M–O bonds, hydroxyl groups, and interlayer carbonate anions (CO₃²⁻), indicating the successful formation of Mg/Al-hydrotalcite. The adsorption distillation process was carried out by varying the adsorption time (1, 3, and 4 hours) using 1 gram of adsorbent. In a separate experiment, adsorbent mass (1, 2, and 3 grams) was varied while maintaining a fixed adsorption time of 4 hours. Gas Chromatography analysis showed that the optimum adsorption time was 4 hours, yielding an ethanol concentration of 19.03%. The optimum adsorbent mass was found to be 3 grams, which increased the ethanol concentration to 33.71%.